Characterization of the cell of origin and propagation potential of the fibroblast growth factor 9‐induced mouse model of lung adenocarcinoma. Issue 4 (17th December 2014) - Arai, Daisuke; Hegab, Ahmed E; Soejima, Kenzo; Kuroda, Aoi; Ishioka, Kota; Yasuda, Hiroyuki; Naoki, Katsuhiko; Kagawa, Shizuko; Hamamoto, Junko; Yin, Yongjun; Ornitz, David M; Betsuyaku, Tomoko
Abstract Fibroblast growth factor 9 (FGF9) is essential for lung development and is highly expressed in a subset of human lung adenocarcinomas. We recently described a mouse model in which FGF9 expression in the lung epithelium caused proliferation of the airway epithelium at the terminal bronchioles and led to rapid development of adenocarcinoma. Here, we used this model to characterize the effects of prolonged FGF9 induction on the proximal and distal lung epithelia, and examined the propagation potential of FGF9‐induced lung tumours. We showed that prolonged FGF9 over‐expression in the lung resulted in the development of adenocarcinomas arising from both alveolar type II and airway secretory cells in the lung parenchyma and airways, respectively. We found that tumour cells harboured tumour‐propagating cells that were able to form secondary tumours in recipient mice, regardless of FGF9 expression. However, the highest degree of tumour propagation was observed when unfractionated tumour cells were co‐administered with autologous, tumour‐associated mesenchymal cells. Although the initiation of lung adenocarcinomas was dependent on activation of the FGF9–FGF receptor 3 (FGFR3) signalling axis, maintenance and propagation of the tumour was independent of this signalling. Activation of an alternative FGF–FGFR axis and the interaction with tumour stromal cells is likely to be responsible for the development of this independence. This study demonstrates the complex role of FGF–FGFR signalling in the initiation, growth and propagation of lung cancer. Our findings suggest that analysing the expressions of FGF–FGFRs in human lung cancer will be a useful tool for guiding customized therapy. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.